Development of a concept for the individualisation of the training process for female pentathletes - S.V. , Sevdalev; E.P. , Vrublevskiy; I.V. , Zavaley (Theory and Practice of Physical Culture, 2026)
Objective of the study is to develop and verify a conceptual framework for the individualization of training for elite female athletes specialising in modern pentathlon. Methods and structure of the study. The research was conducted at the Olympic Sports Laboratory of Skorina Gomel State University. Personalised training models were developed for female pentathletes and tested in the training process of six highly qualified athletes (Master of Sport – International Master of Sport). Model effectiveness was assessed by the magnitude of statistically significant improvements in physical and functional fitness, as well as performance gains in pentathlon disciplines. Results and conclusions. A conceptual framework for the individualization of female athletes’ training in modern pentathlon was developed, incorporating personalised models of competitive activity, annual training cycle structure, and projected dynamics of specialised fitness levels for individual pentathletes, oriented towards achieving target values by the time of major competitions. The practical application of the developed models, based on consideration of individual competitive activity characteristics, morphofunctional and biorhythmological features of a specific athlete’s body, contributed to statistically significant improvements in fitness levels, performance gains in modern pentathlon disciplines, and successful performances at major national and international competitions in the 2024–2025 season.